Chronic Pain and Subjective Health in a Sample of Indonesian Adults: A Moderation of Gender - Weraman, Pius; Susanto, Nugroho; Wahyuni, Luh Tu Selpi; Pranata, Doni; Saddhono, Kundharu; Dewi, Komang Ayu Krisna; Kurniawati, Kadek Lina; Hita, I Putu Agus Dharma; Lestari, Nyoman Ayu Putri; Nizeyumukiza, Emmanuel (Journal of Population and Social Studies [JPSS], 2023)
Chronic pain is an essential burden for public health. Yet, evidence of its association with subjective perceptions of health in the community and gender differences is still lacking in Indonesia. This study examined how chronic pain relates to subjective health in the community and gender differences in this relationship using an Indonesian nationwide community survey. A total of 3,255 adults were involved in the study, with the mean age of the participants being 41.6 years (SD = 13.4), with 57% identifying as female. The results revealed that chronic pain was an essential predictor of subjective health. Those who had chronic pain reported poor subjective health compared to their counterparts, regardless of their gender, education level, marital status, smoking status, unemployment status, religiosity, and extroversion personality trait. In addition, the findings showed that the negative association between chronic pain and subjective health was stronger in women than in men. This study stipulates that targeting pain in the general population and managing and treating pain might lead to improvement in public health. In addition, efforts to reduce chronic pain and to increase subjective health in the general population should be gender mindful.